Pengaruh Perilaku Birokrasi, Disiplin Kerja dan Kualitas Pelayanan terhadap Kepuasan Layanan Wajib Serah Karya Cetak dan Karya Rekam di Perpustakaan Nasional - Kurniwati, Tatat; Hartono, Hartono (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2024)
This study aims to analyze the effect of bureaucratic behavior, work discipline and service quality toward service satisfaction of compulsory submission of printed and recorded works at the National Library. The population of this research is all compulsory submission of printed works and recorded works that receive services at the Deposit Unit of the National Library of Indonesia. The sample in this study are 106 respondents using the probability sampling method, namely simple random sampling, then processed with multiple regression analysis. The independent variables in this study are bureaucratic behavior, work discipline and service quality and the dependent variable is the compulsory submission service satisfaction of printed works and recorded works. The results of this study indicate that bureaucratic behavior has a significant effect on service satisfaction, work discipline has a significant effect on compulsory submission service satisfaction and service quality also has a significant effect on compulsory submission service satisfaction, in simultaneous testing is bureaucratic behavior, work discipline and service quality affect compulsory submission service satisfaction.